Development of protein‐based bioplastics modified with different additives. Issue 42 (28th June 2017) - Felix, M.; Perez‐Puyana, V.; Romero, A.; Guerrero, A.
ABSTRACT: Proteins have been postulated as a feasible source for manufacturing biodegradable polymeric materials. The aim of this study is the development of bioplastic materials from two different protein sources: albumen protein isolated (API), which consists of globular proteins, and crayfish flour (CF), mostly composed of myofibrillar proteins. In order to explore the effect of some chemical reagents on the mechanical properties of the blends and bioplastic materials, two different additives have been used: sodium sulfite (SS) and urea (U). The first one is a reducing agent, and the second one is considered a denaturing agent. The addition of chemical agents induces changes not only in mechanical properties but also in the most suitable processing conditions, which strongly depends on the protein used. Thus, the denaturation of globular proteins seems to lead to a more consistent blend before the injection‐molding process. However, when myofibrillar proteins are used, the processability of the dough‐like material increases after using either SS or U additives. This work illustrates the feasibility of producing animal‐based biodegradable bioplastic materials with different properties and, consequently, different applications, which contribute to adding a high value to two different byproducts from the food industry. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45430. Abstract :